EFEKTIFITAS PEMBELAJARAN MUATAN LOKAL MURADARUSSALAM DALAM PEMBENTUKAN KARAKTER SISWA SMA NEGERI 1 MUARA BELITI KABUPATEN MUSI RAWAS - Yosep Hariansyah (UIN Fatmawati Sukarno Bengkulu, 2020)
This research aims at: 1) to find out the planning process of learning local content Mura Darussalam in the formationof Character Students SMAN 1 mouth of Musi Rawas Regency Beliti 2) To know the implementation of the formation ofCharacter Students SMAN 1 mouth of Musi Rawas Regency Beliti 3) To find out the level of effectiveness of local contentlearning Mura Darussalam in the formation of Character Students SMAN 1 mouth of Musi Rawas Regency Beliti. Thisresearch is the research evaluation. Data analysis techniques are based on a statistical formulation in the form of TSR (high,medium and low). As for the results of this research are as follows: Planning charge Mura Darussalam include: conductingthe identification and analysis of local content, identification and analysis of potential educational unit, determine the typesof local content, determine quiz local content, the school and education service District of Musi Rawas makes learningsyllabus Mulok Mura Darussalam mulok, teacher at the school make Darussalam Mura device learning, next teacher mulokMura Darussalam prepare the learning process. Implementation of the formation of Character Students SMAN 1 mouth ofMusi Rawas Regency, Beliti teacher Mulok Mura Darussalam using Pocket Book has been compiled which Darussalam Muraby the team teachers. To take note of the results of the evaluation, the school provides a list of values to all the teachers init contained hints of pengisisan as well as the processing procedure.Based on the results of the research and the discussionabove, it can be concluded that the effectiveness of learning local content Mura Darussalam in the formation of CharacterStudents SMAN 1 mouth of Musi Rawas Regency Beliti be very effective on the category. This can be known based onrespondents ‘answers score against the now on the implementation of the program been at Darussalam Mura categories veryeffectively as much as 31 respondents (57.4%) and formation of character students SMAN 1 mouth of Musi Rawas RegencyBeliti as many as 30 people respondents answered very effective (55.55%).